Pola Pembelajaran PAI pada Anak Berkebutuhan Khusus Tunarungu - Felzuka, Inayah; Novianto, Chandra; Rahmadani, Fitri; Husna, Difa’ul (Lembaga Yasin AlSys, 2024)
A learning pattern is a way of learning that is taught to students to help them understand and absorb the learning material distributed by educators in order to achieve learning goals. The aim of this article is to explore forms or methods of Islamic education learning that are suitable for children with special needs who are deaf. The method used in this research is library research. Data was collected using documentation techniques from scientific journal articles and books according to topics that have been published online. With a better understanding of the relationship between Islamic education learning patterns and children with special needs who are deaf, it is hoped that this article can provide broad insight into Islamic education learning patterns which are more likely to be accepted by children with special needs who are deaf.